Trusted and Energy Efficient Routing Protocol for Heterogeneous Wireless Sensor Networks (International Journal of Engineering and Computer Science, 2018)
In this paper, we propose STEER for establishing secure trust-value and vitality productive directing convention for Heterogeneous Wireless Sensor Networks. STEER joins Incentive and notoriety based system to enhance the reliability in Heterogeneous Wireless Sensor Networks. The Incentive System includes credits the hubs for relaying packets. The Trust System evaluates the hub's ability and dependability in transmitting packets as far as multi-dimensional trust values. We execute two steering conventions to direct movement through exceedingly trusted hub having adequate vitality to minimize the likelihood of breaking the course. Though there are some current studies in Incentive Schemes, still they are not proficient in either vitality effectiveness or trust value, we proposed a safe convention that insurances Shortest course Path, Maximizing the system life time furthermore the Trust value. By along these lines, STEER can fortify the hubs handoff bundles, as well as keep up course strength and report right vitality ability. This is on the grounds that any loss of trust will bring about loss of future profit. In addition, for the proficient usage of the trust framework, the trust qualities are figured by handling the installment receipts. Systematic results show that STEER a safe the installment and trust figuring without false allegations. Recreation results exhibit that our directing protocols can enhance the packet conveyance proportion and course dependability.